2011
DOI: 10.1177/1470595811413111
|View full text |Cite
|
Sign up to set email alerts
|

HR practices during post-merger conflict and merger performance

Abstract: An extensive body of literature has investigated financial and strategic variables as predictors of mergers and acquisitions (M&A) performance without finding clear relationships. The literature does not investigate remedies for conflicts in M&A. This paper aims to develop a knowledge-based theory of M&A integration, drawing upon research on HR practices in M&A, the resource-based view of the firm, and international management. The study also explores the critical differences between acquirers from various cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 82 publications
4
75
0
Order By: Relevance
“…However, employees coming with a cultural background that 7 emphasizes a culture of weak uncertainty avoidance and low power distance will probably perform better with experiential training techniques, such as on-the-job training. According to Weber, Rachman-Moore, and Tarba (2012) this may explain the positive relationships found between on-the-job training and performance of the Danish acquirers (characterized by low uncertainty avoidance and low power distance). Similarly, it may elucidate on the negative relationship between on-the-job training and performance of Belgian acquirers (characterized by high in uncertainty avoidance and high power distance).…”
Section: Literature Review Hr Practices During Post-manda Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, employees coming with a cultural background that 7 emphasizes a culture of weak uncertainty avoidance and low power distance will probably perform better with experiential training techniques, such as on-the-job training. According to Weber, Rachman-Moore, and Tarba (2012) this may explain the positive relationships found between on-the-job training and performance of the Danish acquirers (characterized by low uncertainty avoidance and low power distance). Similarly, it may elucidate on the negative relationship between on-the-job training and performance of Belgian acquirers (characterized by high in uncertainty avoidance and high power distance).…”
Section: Literature Review Hr Practices During Post-manda Integrationmentioning
confidence: 99%
“…This is particularly the case for crossborder M&As (Weber and Tarba, 2010). After exploring the critical differences between acquirers from various countries in the way in which HR is managed in cross-cultural conflict situations, and after examining the relationship between HR practices and post-merger performance in different countries, Weber, Rachman-Moore, and Tarba (2012) concluded that there is no clear best practice to address the conflict situation and to enhance M&A performance.…”
Section: Literature Review Hr Practices During Post-manda Integrationmentioning
confidence: 99%
“…1Others [Weber, Rachman-Moore & Tarba, 2012;Gomes et al, 2013] indicate that much has been written about the financial, strategic, and integration aspects of M&A, but the findings are contradictory and the reasons for variations in M&A performance have remained unclear, probably because of the focus on premerger variables, thereby neglecting cross-cultural conflicts between people in the post-merger period.…”
Section: Mergers and Acquisitionsmentioning
confidence: 99%
“…Additionally, legal issues have hardened the process of cross-border mergers (Gogan, Baxter, Boss, & Chircu, 2013). Furthermore, cultural clashes are still a very sensitive aspect in cross-border mergers and a common reason for M&A transactions to fail (Halsall, 2008;Weber, Rachman-Moore, & Tarba, 2012). Was it originally First World corporations seeking to invest in emerging markets such as Brazil, Russia, India, and China (henceforth BRIC) for resource reasons, Caiazza and Volpe (2015) are studying a new reversed trend: emerging country corporations are investing in developed countries through M&A activities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There have been different approaches investigating motives (Arnold & Parker, 2009;Berkovitch & Narayanan, 1993;Nguyen et al, 2012;Trautwein, 1990), synergies (Chatterjee, 2007;Damodaran, 2005;Ficery et al, 2007;Garzella & Fiorentino, 2014;Goold & Campbell, 1998;Kode et al, 2003), PMI (Adams & Neely, 2000;Angwin & Meadows, 2015;Datta, 1991;Joseph, 2014;Weber et al, 2012), evaluation methods (Ahammad & Glaister, 2013;Calandro et al, 2007;Kode et al, 2003), etc.. Referring to timing concepts, only speed has been investigated in more detail, stating that there is a limited time frame to realise synergies after closing (Angwin, 2004;Bert et al, 2003).…”
Section: Comparing To Literaturementioning
confidence: 99%